2013
DOI: 10.1371/journal.pone.0064294
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation Shifts Preferred Orientation of Tuning Curve in the Mouse Visual Cortex

Abstract: In frontalized mammals it has been demonstrated that adaptation produces shift of the peak of the orientation tuning curve of neuron following frequent or lengthier presentation of a non-preferred stimulus. Depending on the duration of adaptation the shift is attractive (toward the adapter) or repulsive (away from the adapter). Mouse exhibits a salt-and-pepper cortical organization of orientation maps, hence this species may respond differently to adaptation. To examine this question, we determined the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 43 publications
(70 reference statements)
8
42
0
Order By: Relevance
“…A part of the remaining population refracted the adapter and did not show any significant shift (< 5°) in orientation tuning (Bachatene et al ., , ; Jeyabalaratnam et al ., ). The corresponding proportion of repulsive shifts for both layers was found to be comparable (06 neurons in supra‐ and 07 in infragranular layers).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A part of the remaining population refracted the adapter and did not show any significant shift (< 5°) in orientation tuning (Bachatene et al ., , ; Jeyabalaratnam et al ., ). The corresponding proportion of repulsive shifts for both layers was found to be comparable (06 neurons in supra‐ and 07 in infragranular layers).…”
Section: Resultsmentioning
confidence: 97%
“…A proportion analysis was not performed on these latter datasets as we were primarily interested in comparing only attractive and repulsive behaviors across layers. Such novel selectivity has been reported previously in mice (Jeyabalaratnam et al ., ). It is to be underlined that neurons with an orientation selectivity index (OSI) < 0.5 were classified as untuned (Bharmauria et al ., , ).…”
Section: Resultsmentioning
confidence: 99%
“…Some SU demonstrated strong tuning curves, but others did not. However, it has been well characterized that in primary visual cortex, many neurons do not exhibit strong tuning preferences, such as luminance, adaptation, position, and contrast cells(Antolik and Bednar, 2011; Dai and Wang, 2012; Gavornik and Bear, 2014; Harding and Fylan, 1999; Jeyabalaratnam et al, 2013; Niell and Stryker, 2008; Vetter et al, 2014). Therefore, this work focuses on longitudinal characterization of broad evoked firing rate changes.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this work focuses on longitudinal characterization of broad evoked firing rate changes. Furthermore, without a tetrode configuration or intracellular electrodes, a single recording site cannot discriminate between two SU with similar waveforms but distinct tuning curves, which is further complicated by the salt-and-pepper organization of the rodent cortex(Jeyabalaratnam et al, 2013). In addition, previous studies have demonstrated that the awake cortex is dominated by inhibition(Haider et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation